The role of related humor in facilitating instructional information processing in video lectures : insight from EEG - Weichen, Zhou; Jun Choi, Lee (Springer Nature, 2025)
Related humor is a well-established pedagogical strategy in traditional education; however, its impact on learning from video lectures has been understudied. This study investigated whether related humor, as predicted by Instructional Humor Processing Theory (IHPT), enhances learning in a video-based educational context. Employing a within-subjects design, 25 undergraduate students viewed two video lectures presenting distinct sets of English vocabulary words, each illustrated with either related humorous or related neutral instructional information. Electroencephalography (EEG) signals were recorded while participants viewed the illustrative information, and self-reported learning experiences (motivation, elaboration) and learning performance (recall) were assessed post-lecture. Paired samples t-tests revealed that video lectures incorporating related humorous information outperformed those with related neutral information, as evidenced by increased EEG beta and theta band oscillations, higher motivation scores, and superior recall performance. While related humor elicited greater neural activation associated with memory encoding, no differences were observed in self-reported elaboration between conditions. Taken together, these findings highlight the unique benefits of related humor in facilitating learners’ processing of instructional information within the context of video lectures. Future research should continue to explore the effects and boundaries of related humor, considering variations in humor format and delivery method